Diagnosing Kaposi’s Sarcoma (KS) in East Africa: how accurate are clinicians and pathologists? - Amerson, Erin; Buziba, Nathan; Wabinga, Henry; Wenger, Megan; Bwana, Mwebesa; Muyindike, Winnie; Kyakwera, Catherine; Laker, Miriam; Mbidde, Edward; Yiannoutsos, Constantin; Wools-Kaloustian, Kara; Musick, Beverly; et al. (Infectious Agents and Cancer, 2012)
HIV-associated KS is the most common reported malignancy in sub-Saharan Africa, and appropriate therapy of KS requires accurate diagnosis. In much of the region, however, KS diagnosis is limited to clinical suspicion without pathologic confirmation. Where pathology is available, specific anti-KSHV stains are rarely available and overall pathologic accuracy for KS has not been evaluated.
Keywords: HIV; Kaposi’s Sarcoma; Diagnosis; Clinicians and pathologists